Determinasi Teknologi Komunikasi dan Adaptasi Media Pembelajaran di Masa Pandemi COVID-19 - Mellisa Fransisca; Rizki Briandana (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2022)
Ukrida has implemented an online learning system starting March 23, 2020 as an effort to control the spread of the Covid-19 virus. Technological changes in the learning system from face-to-face to online "force" educators to adapt to the determination of technology in terms of online learning media. University leadership has determined the Ukrida Virtual Class (UVC) as a learning media that must be used by educators in running the online learning system during the Covid-19 pandemic. The purpose of this study was to analyze the adaptability of educators to the determination of technology in terms of the use of UVC as online learning media during the Covid-19 pandemic. The research methodology uses a post-positivism paradigm with a qualitative approach. The post-positivism paradigm is used to see the phenomenon of determination of technology that "forces" educators to adapt the implementation of online learning system during the Covid-19 pandemic. The results of the study show that the adaptation of educators to UVC at the beginning of the at Even Semester 2019/2020, is still very minimal both in the number of educators and the ability to take advantage of all the features in UVC. But over time, with the implementation of policies issued by the University to support optimal use of UVC, it shows that the number of educators who use UVC in the following semester is increasing. Researchers also found that Ukrida already has two of the three components of online learning, namely the e-learning learning model (a) which is applied in the current learning system with a Moodle-based learning management system (LMS) and Ukrida Virtual Class as an online learning medium (c) while learning instructional design strategies (b) are currently being developed by the learning resources center (LRC), known as the Materials and Learning Innovation Development Unit (PMIP).